Detection of Helicobacter pylori IgG in diabetic patients and non-diabetic - A.A. Al-Abdul (University of Thi-Qar Journal of Science, 2019)
Diabetes mellitus is one of the important causes of dyspepsia. The incidence of H. pylori is increased in diabetes mellitus. A total of ninety two (92) blood samples which include sixty two (62) samples for diabetic patient and thirty (30) samples non-diabetic as a control from November 2012 – March 2013 in private laborotary (Ibn- Alnafes) in Basra city. All samples were subjected to assessment of fasting blood sugar (FBS) level and detection of H. pylori antibodies (H. pylori IgG)# by enzyme linked immunoabsorbent assay (ELIZA). The highest frequency of H.pylori was in diabetic patients 54/62(87%), while non diabetic patients (as control), was 3/30(10). Statistically the differences were significant (P < 0.05) among diabetic and non-diabetic patients with H. pylori. For the diabetic patients, of the total 37/62(60%) males, 32/37(86%) showed positive test for H. pylori IgG, while 22/25(88%) out of 25/62( 40 %) females, showed positive test of for H. pylori IgG, but the difference was statistically non significant (P > 0.05).For non diabetic group, of the total 18/30(60 %) males, 2/18(11%) showed positive test for H. pylori, and of the total 12/30( 40%) females, 1/12(8%) showed positive test for H.pylori IgG but the differences was statistically non significant (P > 0.05) Age of patients and control range from 20-80 years, for diabetic and non-diabetic patients, the highest detection rates of H. pylori IgG was recorded in the age group (41-60) years, 33/37(89%) and 2/10(20%) respectively, while the lowest detection rate were recorded in the age group (20-40) years, 10/13(77%) and 0/10(0%) respectively. Statistically, the differences was significant (P < 0.05) among these age groups.